Is the core-periphery labour market structure related to perceived health? findings of the Northern Swedish Cohort - Waenerlund Anna-Karin; Gustafsson Per E; Virtanen Pekka; Hammarström Anne (BMC, 2011)
Abstract Background There is controversy as to whether peripheral employment is related to poor health status or not. This study aims at examining whether 1) the accumulation of time in peripheral labour market positions is associated with psychological distress and poor or average self-rated health; 2) the proposed association is different among women than among men. Method Participants in the 1995 and 2007 follow-up surveys of the Northern Swedish Cohort (n = 985) completed self-administered questionnaires about psychological and general health and about employment positions during the follow-up years. Associations between 12 year peripheral labour market positions (no, low, medium and high exposure) and health were examined using logistic regression. Results Exposure to peripheral employment was positively related to psychological distress in both women and men (p-values for trend < 0.001). Adjustment for sociodemographics and psychological distress at baseline, as well as for unemployment and being out of the labour market at the follow-up, resulted in attenuation of the odds ratios, particularly in the group with high exposure to peripheral employment, although results remained significant in men in the fully adjusted model. Women and men with high exposure to peripheral employment had high odds of poor or average self-rated health, but the association was rendered non-significant after adjustment for the covariates. Conclusions Our findings suggest that exposure to peripheral employment positions has an impact particularly on mental health, partly due to the over-representation of other unfavourable social and employment conditions among those with substantial exposure to peripheral employment.